A serial mediation model of the relationship between cybervictimization and cyberaggression: The role of stress and unforgiveness motivations - Quintana-Orts, Cirenia Luz; Rey-Peña, Lourdes; Chamizo-Nieto, María Teresa; Worthington Jr., Everett L. (MDPI, 2020)
Cyberaggression is often triggered by cybervictimization. However, little attention has been given to the underlying mechanisms in this relationship. Specifically, this study examined the mediating roles of stress as well as unforgiveness (i.e., revenge and avoidance motivations) in the cybervictimization-cyberbullying aggression link. The main goal is to investigate the direct and indirect effects of cybervictimization on cyberbullying aggression while modeling a process in which cybervictimization causes stress, which in turn causes unforgiveness motivations concluding with cyberbullying aggression as the consequent. A total of 979 adolescents (Mage = 13.72, SD = 1.31) completed the relevant scales at two time points spaced four months apart. The results confirm that stress and revenge motivation at Time 1 act as serial mediators between cybervictimization at Time 1 and cyberbullying behaviors at Time 2. Additionally, the results reveal that avoidance at Time 1 was not a significant mediator in the links between cybervictimization at Time 1 and cyberbullying aggression at Time 2. Our findings provide support for the stress-and-coping model of forgiveness in adolescence and offer original insight into the developmental process of bully-victims in cyberbullying context. These results suggest the importance of efforts addressing motivations and emotion-focused coping strategies in adolescents who have been bullied to prevent and reduce those adolescents’ future stress and aggressive behaviors. The contributions and implications of the results are discussed.
Keywords: Ciberacoso; Perdón; Internet y jóvenes; Adolescentes - Salud mental; Cyberbullying; Aggression; Victimization; Stress; Unforgiveness motivations; Stress and coping